Comparative cost-effectiveness of three post-radiofrequency ablation surveillance intervals for Barrett’s esophagus - Menon, Shyam; Norman, Richard; Mannath, Jayan; Iyer, Prasad G.; Ragunath, Krish (Endoscopy International Open, 2022)
Background and study aims Radiofrequency ablation (RFA) for dysplastic Barrett’s esophagus (BE) has resulted in a paradigm shift in the management of BE. Despite widespread adoption of RFA, the optimal surveillance interval of the ablated zone is unclear.Methods A patient-level discrete time cycle Markov model was developed to model clinical surveillance strategies post-RFA for BE. Three surveillance strategies were examined: the American College of Gastroenterology (ACG) strategy based on ACG guidelines for post-RFA surveillance, the Cotton strategy based on data from the USA and UK RFA registries, and the UK strategy in line with surveillance strategies in UK centers. Monte-Carlo deterministic and probabilistic analyses were performed over 10,000 iterations (i. e., representing 10,000 patient journeys) and sensitivity analyses were carried out on the variables used in the model.Results On base-case analysis, the ACG strategy was the most cost-effective strategy, at a mean cost of £ 11,733 ($ 16,396) (standard deviation (SD) 1520.15) and a mean effectiveness of 12.86 (SD 0.07) QALYs. Probabilistic sensitivity analysis demonstrated that the ACG model was the most cost-effective strategy with a net monetary benefit (NMB) of £ 5,136 ($ 7177) (SD 241) compared to the UK strategy and a NMB of £ 7017 ($ 9,806) (SD 379) compared to the Cotton strategy. At a willingness to pay (WTP) threshold of £ 20,000 ($ 27,949), the ACG model was superior to the other strategies as the most cost-effective strategy.Conclusions A post-RFA surveillance strategy based on the ACG guidelines seems to be the most cost-effective surveillance option.